Nondestructive, real time technique for in-plane heat diffusivity measurements. (June 2020) - Adamczyk, Wojciech; Białecki, Ryszard; Orlande, Helcio R.B.; Ostrowski, Ziemowit
Highlights: A real-time, nondestructive measurement technique for measuring the in-plane thermal diffusivity of massive, flat orthotropic, and isotropic bodies. Flash laser heating and IR camera utilized with the outputted results being independent of the surface emissivity and absorbed laser radiation. Deterministic and Bayesian methods for retrieving thermal diffusivity applied. The technique is applicable to a wide range of diffusivities. Abstract: A new technique and device for measuring in-plane heat diffusivity for isotropic and orthotropic media are proposed. This novel method is associated with active thermography, with a laser flash generating temperature changes in the sample and the utilization of an infra-red camera to observe these changes. The model is a semi-infinite body with an adiabatic boundary heated by a Dirac delta impulse. Instead of recording the spatial and temporal changes of the surface temperature, only the time instant at which the intensity of radiation attains a maximum at a selected set of points is recorded and processed. The approach does not require assessment of two, difficult to measure, quantities: the surface emissivity and the amount of heat absorbed by the sample as a result of the laser flash. The time of the measurement is on the order of a second. The solution is a surprisingly simple expression linking the time, at which the temperature attains its maximum, with the diffusivity of the sample. This model has been used to solve the inverse problem of retrieving the diffusivity using the standard least squares method and the Bayesian Monte Carlo Markov Chain technique. The results compare well with those obtained using a commercial Parker flash method equipment.